Effect of Internal Heat Generation/Absorption on Dusty Fluid Flow over an Exponentially Stretching Sheet with Viscous Dissipation - G. M. Pavithra; B. J. Gireesha (Journal of Mathematics)
A numerical analysis has been carried out to describe the boundary layer flow and heat transfer of a dusty fluid over an exponentially stretching surface in the presence of viscous dissipation and internal heat generation/absorption. The governing partial differential equations are reduced to nonlinear ordinary differential equations by a similarity transformation, before being solved numerically by Runge-Kutta-Fehlberg 45 method. The heat transfer analysis has been carried out for both PEST and PEHF cases. The numerical results are compared with the earlier study and found to be in excellent agreement. Some important features of the flow and heat transfer in terms of velocities and temperature distributions for different values of the governing parameters like fluid-particle interaction parameter, Prandtl number, Eckert number, Number density, heat source/sink parameter, and suction parameter which are of physical and engineering interests are analyzed, discussed, and presented through tables and graphs.